2021
DOI: 10.6118/jmm.20036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Drinking Water on Bone Density of Postmenopausal Women with Osteoporosis

Abstract: Objectives Postmenopausal women are predisposed to osteoporosis, and those on acidic diets are at a higher risk, because it has been demonstrated that such diets have adverse effects on bone health. In this study, the effect of alkaline drinking water on bone mineral density was evaluated in postmenopausal women with osteoporosis. Methods One hundred postmenopausal women with osteoporosis (T-score ≤ −2.5) were equally divided into an intervention group and a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Indeed, in vitro and in vivo experiments have proved the efficacy of alkaline Ca-rich water to favor bone matrix affixing [13]. At the same time, several clinical studies have demonstrated that bicarbonate-calcic water is an efficacious nutritional supplement to preserve an adequate Ca content in pathological conditions characterized by bone matrix loss [46,47]. While all these data demonstrate the efficacy of bicarbonate-calcic water on Ca metabolism and bone status [6,13,48], data regarding the impact of bicarbonate-calcium water supplements on the systemic metabolic balance are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in vitro and in vivo experiments have proved the efficacy of alkaline Ca-rich water to favor bone matrix affixing [13]. At the same time, several clinical studies have demonstrated that bicarbonate-calcic water is an efficacious nutritional supplement to preserve an adequate Ca content in pathological conditions characterized by bone matrix loss [46,47]. While all these data demonstrate the efficacy of bicarbonate-calcic water on Ca metabolism and bone status [6,13,48], data regarding the impact of bicarbonate-calcium water supplements on the systemic metabolic balance are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline water has been known to positively impact bone health as well as reverse effects of aging. It is also believed that alkaline water improves spine T score in premenopausal women [28]. The results of a study involving aged mice which were treated with alkaline water and regular tap water and then sampled at postmortem after 24 months suggested that mice watered with alkaline water overwhelmed control mice.…”
Section: Discussion Hydrogen Ion Concentration/phmentioning
confidence: 99%
“…Additionally, low mineral content in drinking water, such as calcium and magnesium, has been found to have various adverse health impacts. Associated health risks include an increased risk of cardiovascular disease [18][19][20][21][22][23], caries [24,25], osteoporosis [26,27] and potentially various cancers [28][29][30][31][32][33]. This could be relevant in the Gaza Strip because of the high consumption of desalinated water [4].…”
Section: Potential Health Risks Associated With Drinking Water Qualit...mentioning
confidence: 99%